2016
DOI: 10.1002/mbo3.346
|View full text |Cite
|
Sign up to set email alerts
|

The HigB/HigA toxin/antitoxin system of Pseudomonas aeruginosa influences the virulence factors pyochelin, pyocyanin, and biofilm formation

Abstract: Toxin/antitoxin (TA) systems are prevalent in most bacterial and archaeal genomes, and one of the emerging physiological roles of TA systems is to help regulate pathogenicity. Although TA systems have been studied in several model organisms, few studies have investigated the role of TA systems in pseudomonads. Here, we demonstrate that the previously uncharacterized proteins HigB (unannotated) and HigA (PA4674) of Pseudomonas aeruginosa PA14 form a type II TA system in which antitoxin HigA masks the RNase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 72 publications
2
128
0
Order By: Relevance
“…GraT inhibits ribosome biogenesis by directly interacting with DnaK (a known facilitator of late stage ribosome biogenesis) or by attacking an unknown target (Ainelo et al, ). Although the exact targets of the endonuclease activity of HigB in PAO1 remain to be elucidated, an in vitro cleavage assay using ompA and ompF mRNAs as substrates in P. aeruginosa PA14 showed that HigB exhibits mRNase activities (Wood and Wood, ) and HigB reduces the intracellular c‐di‐GMP level by affecting c‐di‐GMP metabolism genes (Zhang et al, ). In addition, using a DNA microarray study and a PA14 transposon mutant ( MAR2×T7 transposon insertion), the activation of HigB due to transposon insertion in higA was found to reduce the expression of pyochelin and pyochelin‐related genes in PA14 (Wood and Wood, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GraT inhibits ribosome biogenesis by directly interacting with DnaK (a known facilitator of late stage ribosome biogenesis) or by attacking an unknown target (Ainelo et al, ). Although the exact targets of the endonuclease activity of HigB in PAO1 remain to be elucidated, an in vitro cleavage assay using ompA and ompF mRNAs as substrates in P. aeruginosa PA14 showed that HigB exhibits mRNase activities (Wood and Wood, ) and HigB reduces the intracellular c‐di‐GMP level by affecting c‐di‐GMP metabolism genes (Zhang et al, ). In addition, using a DNA microarray study and a PA14 transposon mutant ( MAR2×T7 transposon insertion), the activation of HigB due to transposon insertion in higA was found to reduce the expression of pyochelin and pyochelin‐related genes in PA14 (Wood and Wood, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these strains, highly conserved higBA loci are not only found in Pseudomonas aeruginosa but are also present in 26 other Pseudomonas strains, such as P. syringae, P. putida and P. fluorescens (53%-86% identity for higA and 63%-86% identity for higB). Among the identified loci, the recently characterized PA14_RS25265 and Rorf_67641 genes in P. aeruginosa PA14 (Li et al, 2016;Wood and Wood, 2016) are the same as HigB/HigA in PAO1. The GraTA TA system in P. putida KT2440 has been identified as a novel temperature-dependent TA pair (Tamman et al, 2014), and the antitoxin GraA has 56% identity with HigA in PAO1, whereas GraT has 70% identity with HigB in PAO1 (Fig.…”
Section: Gene Idmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive suite of virulence genes was determined by utilising the Pseudomonas Genome Database (http://www.pseudomonas.com/) [195]. For the HigB toxins, primer sequences were obtained and blasted to identify the gene product [116]. For a gene to be considered present searching required 100% of the gene to be present in the BLAST output.…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…In 2016 Wood et al also described a type two toxin/anti-toxin system in P. aeruginosa consisting of the proteins HigB and HigA. The role of this system is to regulate bacterial toxicity [116].…”
Section: Update On P Aeruginosa Blood Stream Infectionmentioning
confidence: 99%